Recognition and empathy through television series. The case of Daenerys Targaryen of Game of Thrones - Vázquez Parra, José Carlos (2019)
The contemporary reality demands from the teachers the need to be updated in everything related to the teaching of the new generations. Therefore, the identification of new learning spaces is a valuable tool in the face of these new demands. This article aims at exposing a learning experience in a group of university students from a private institution in the city of Guadalajara, Mexico, in which, through the use of fictional characters from a television series, one can contribute to the development of Ethical sub-competences of recognition and empathy, demonstrating that the formation of transversal competences can be generated in multiple ways, and not only through theoretical reflection. As a case study, an analysis of the profile and history of the character Daenerys Targaryen of the television drama Game of Thrones has been made.